Lean green study of the impact of lean on the environmental performance of nordic companies and comparison with results from Portuguese companies - Vasconcelos, Margarida Dias Martins Jácome de (2024)
The negative environmental impacts caused by unmeasured human activity over the years are the main cause of global warming. Stakeholders are growingly aware of the consequences these results can have on both people and the planet and are seeking options that satisfy their needs with the least possible impacts. In other words, customers are looking for environmentally sustainable organisations (that is, Green organisations), which means that companies need to adapt their processes to comply with the new requirements and remain competitive, without compromising their financial objectives. Researchers often debate whether the integration of the Lean philosophy and Green leads to additional benefits. Building on a previous study regarding the impacts of the implementation of Lean practices on the environmental performance of Portuguese organisations and given the importance of a global change to greener behaviours, this dissertation aims to study the impacts of the implementation of Lean practices on the environmental performance of Nordic organisations by answering the research question, “Does the implementation of Lean tools/methods/concepts impact the environmental performance of organisations?”. To do so, an extensive and detailed systematic literature review was conducted, and a conceptual framework was developed with the findings. Further, a survey questionnaire was sent out to 2486 companies in Denmark, Finland, Iceland, Norway and Sweden. From the 163 responses received, 140 were considered valid and underwent a process of data analysis, in which statistically significant correlations between pairs of variables were studied and the results were compared to the conclusions drawn from a study conducted in the Portuguese industrial context. On one hand, the findings regarding the operational impacts showed statistically significant correlations between the improvement of the organisation’s image and its activity time, and between the extent of time the organisation has been implementing Lean practices and the reduction of costs, the reduction of defective products, the improvement of delivery times, and the improvement of product quality. On the other hand, the findings regarding the environmental impacts showed a statistically significant correlation between the extent of time the organisation has been implementing Lean practices and the reduction of solid waste production.